EDUKASI PENCEGAHAN PENULARAN COVID-19 BAGI TENAGA KESEHATAN DAN PASIEN DI POLIKLINIK RAWAT JALAN OBSGIN - Brahmana, Ivanna Beru (Jurnal EMPATI (Edukasi Masyarakat, Pengabdian dan Bakti), 2020)
Pregnant women need antenatal care (ANC) examinations aimed at fetal health and maternity readiness. Pandemic conditian make ANC implementation could not match the control schedule. This is done so that health workers avoid Covid-19 infection and serving ANC patients who may not be postponed or rejected. Providing education on the prevention of the spread of Covid-19 for health workers and patients at the Obsgyn outpatient polyclinic. Filling out a questionnaire about the patient's knowledge of Covid-19; limited lectures with social distancing conducted to 5-6 collected patients; and providing education on how to wash hands and use masks correctly. The total participants who were given education was 100 people. All participants 100% (100/100) understand about the Covid-19 virus, stay at home, maintain a minimum distance of 1 meter (social distancing), use mask, and wash their hands or use a hand sanitizer. It was different when the respondents came to clinic and assessed by the Nurse what they did was found: 100% (100/100) understood about the Covid-19 disease, 94% (94/100) stayed at home, 100% (100/100) kept their distance at least 1 meter (social distancing), 75% (75/100) wear a mask properly, and 60% (60/100) wash their hands or bring a hand-sanitizer.